2017
DOI: 10.1177/0962280217718866
|View full text |Cite
|
Sign up to set email alerts
|

Two-way partial AUC and its properties

Abstract: Simultaneous control on true positive rate (TPR) and false positive rate (FPR) is of significant importance in the performance evaluation of diagnostic tests. Most of the established literature utilizes partial area under the receiver operating characteristic (ROC) curve with restrictions only on FPR, called FPR pAUC, as a performance measure. However, its indirect control on TPR is conceptually and practically misleading. In this paper, a novel and intuitive performance measure, named as two-way pAUC, is prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(38 citation statements)
references
References 16 publications
0
34
0
Order By: Relevance
“…Not every statistically significant difference in the mean value of a given parameter (e.g., microRNA [miRNA] level in plasma) between two groups justifies its use as a diagnostic biomarker for epileptogenesis. The usefulness of a diagnostic test is commonly evaluated using statistical measures such as the true positive rate (i.e., sensitivity), false positive rate (1-specificity), receiver operating characteristic (ROC) curve, and area under the ROC curve (AUC) (Ma et al, 2015;Yang et al, 2017). Sensitivity measures the proportion of correctly identified subjects having the specific condition or disease.…”
Section: Biomarker Discovery Process and Statisticsmentioning
confidence: 99%
“…Not every statistically significant difference in the mean value of a given parameter (e.g., microRNA [miRNA] level in plasma) between two groups justifies its use as a diagnostic biomarker for epileptogenesis. The usefulness of a diagnostic test is commonly evaluated using statistical measures such as the true positive rate (i.e., sensitivity), false positive rate (1-specificity), receiver operating characteristic (ROC) curve, and area under the ROC curve (AUC) (Ma et al, 2015;Yang et al, 2017). Sensitivity measures the proportion of correctly identified subjects having the specific condition or disease.…”
Section: Biomarker Discovery Process and Statisticsmentioning
confidence: 99%
“…In these cases, pAUC FPR could favor either ROC curve, depending on not well-meditated or not well-understood choices of q 1 and q 2 . Also, as observed by Yang et al, 7 explicitly constraining FPR results in implicitly constraining TPR as well. Take the ROC curve for concavitySE: constraining FPR between 0.1 and 0.3 entails accepting TPR in the [0.25, 0.75] range.…”
Section: The Importance Of Delimiting the Region Of Interestmentioning
confidence: 53%
“…We now show by means of examples why, to meaningfully assess and compare the diagnostic performances of tests, it is very important to delimit the part of the ROC space that needs to be taken into account, which we call the region of interest (RoI) in our proposal. 2 We use the same example used by Yang et al 7 , based on the Wisconsin Breast Cancer Data (Diagnostic) from the UCI Machine Learning Repository. 8 This dataset records diagnosis results of breast cancer, in which 30 biomarkers are measured from 469 subjects (189 malignant and 280 benign).…”
Section: The Importance Of Delimiting the Region Of Interestmentioning
confidence: 99%
“…25 To reduce variance, a bootstrapping procedure was used 2000 times to validate the best AUC values and 95% CIs for MetS. 26 Moreover, the comparisons of AUC values were performed using the method of DeLong et al 27 and the optimal cut-off value was identified using the maximum value of Youden's index, which is calculated by sensitivity (Sen) plus specificity (Spe) minus 1.…”
Section: Discussionmentioning
confidence: 99%